Moving to Map and Mapping to Move: The East Africa Colonial Itineraries of the IGMI Archives and Library as a Special Genre in Cartography - Ciampi, Gabriele (Aethiopica, 2015)
Colonial Itineraries represent an informative product that has its origins in the innovative military organization of Revolutionary and Napoleonic France. Italian Colonial Itineraries were the outcome of exploration and intelligence activities carried out by selected military units in unknown lands. The knowledge of the places was an essential precondition of conquest and its stabilization. The major feature of the itineraries is the juxtaposition of a reconnaissance map to a list of detailed information concerning every short stretch of route covered: running times, road conditions, climate, landforms, land-use, water resources, culture, economy, monuments, etc. The Archives and the Library of the IGMI (Istituto Geografico Militare Italiano), set in Florence, preserve a great deal of such documents and they are probably the richest Italian stock. Itineraries represent a valuable source of geographical knowledge about Ethiopia and Eritrea during the period between the late nineteeth and the thirties of the twentieth century. These pages are the result of an attempt at census and interpretation.